PrabotulinumtoxinA vs OnabotulinumtoxinA for the Treatment of Adult Males With Moderate to Severe Glabellar Lines: Post-hoc Analyses of the Phase III Clinical Study Data. (4th August 2022) - Solish, Nowell; Ascher, Benjamin; Avelar, Rui L; Bertucci, Vince; Bodokh, Isaac; Carruthers, Jean; Cartier, Hugues; Delmar, Henry; Denfeld, Ralf; Heckmann, Marc; Hedén, Per; Hilton, Said; et al.
Abstract: Background: Despite a growing interest among men in cosmetic procedures such as botulinum toxin, comparator clinical trial data in this population are limited. Objectives: The authors sought to compare the efficacy and safety of prabotulinumtoxinA and onabotulinumtoxinA for the treatment of males with moderate to severe glabellar lines. Methods: Post-hoc analyses were performed on the subpopulation of male patients treated with either a single dose of 20 U prabotulinumtoxinA (n = 25) or 20 U onabotulinumtoxinA (n = 31) in the EVB-003 Phase III glabellar line clinical study. One key efficacy endpoint was the proportion of responders with a ≥1-point improvement from baseline at maximum frown on the 4-point Glabellar Line Scale. Results: Compared with onabotulinumtoxinA-treated males, the percentages of responders who had a ≥1-point improvement on the Glabellar Line Scale at maximum frown were higher at all postbaseline time points for prabotulinumtoxinA-treated males ( P > 0.05 at all visits) by an absolute overall mean difference of 10.1% across all visits. Similar trends were observed for efficacy endpoints based on global aesthetic improvement and subject satisfaction. PrabotulinumtoxinA-treated males had a higher incidence of treatment-related headache and eyelid ptosis. Conclusions: The percentages of patients who met the definition of a responder were higher at almost all time points examined for prabotulinumtoxinA-treated males. Despite the high level of consistency across all measures, differences between the 2 treatment groups did not reach statistical significance. Further study is warranted to establish if these post-hoc analyses observations are reproducible in a larger male patient population. Level of Evidence: 1: